Nursing in a critical care hyperbaric unit at Merida, Yucatan, Mexico: report of a case of an acute pediatric burn patient - Ruiz-Aguilar, Judith; Diaz-Ibañez, Rodrigo; Sanchez-Rodriguez, E. Cuauhtemoc (Journal of Emergency and Critical Care Medicine, 2019)
Hyperbaric oxygen therapy (HBOT) for intensive care unit (ICU) patients places special technical and knowledge-based skills demands on nurses inside hyperbaric chambers. Probably the best clinical contributions of HBOT are in the acute cases, in the ischemia reperfusion injury. Nevertheless in the last years, hyperbaric units have focused more in chronic wounds. The first golden rule to treat an ICU patient in a hyperbaric chamber is that you can maintain the same quality of care inside the chamber as in the ICU. This means that the hyperbaric unit has to have the technology means as well as the proficiency and competency of its personnel to provide intensive care inside the chamber. These require competent nursing personnel. We present a case of a 5-year-old pediatric patient who suffered a deep second-degree thermal burn that compromised 32% of the total body surface; including the face, neck, thorax and both arms. The patient received medical support, HBOT and daily wound care. He received a total of 14 treatments and underwent complete healing of the burned areas. The hospital stay was of 17 days, which is lower than expected for a severe burned patient (average of 27.5±1.2 days). He experienced neither secondary effects nor complications. The management of ICU patients inside the chamber requires an experienced and competent team of physicians and nurses. When instituted early, HBOT in the management of thermal burns, makes great impact in the pathophysiology, reduction of surgical procedures and hospital stay.